The lived experience of families with a mentally ill family member - Wankiiri, Moses; Drake, Karen B.; Meyer, Kimberley R. (Journal of Research in Nursing and Midwifery, 2013)
The study of the lived experience of families with a mentally ill family member involved seven family members who had come to visit their mentally ill relatives in the mental Hospital. The major objective was to explore the lived experience of families with a persistent1 mentally ill family member. The study adopted a qualitative descriptive-phenomenological design, participants were purposively sampled and data was collected using a tape recorder. Colaizzi’s phenomenological approach for data management was then employed. The study revealed that family members held misconceptions about mental illness and described care as a contractual obligation. They lived in misery as the patients’ behavior was intolerable, sadistic, exasperated, and embarrassing. Although medication proved helpful, they had to plead with the patient to take it. Their homes were discriminated2 which made them desperate and disappointed. Patients had bizarre complaints, could vanish, which forced family members to be vigilant all the time and made them feel guilty if anything happened to the patient. Family revenue was devastated and admission of the patients was considered a liberty to the family members and a break from the monotonous, tiresome and costly collection of medication from the hospital. Family members were pessimistic, and always in dilemma. Living with a mentally ill family member was considered a prime issue in the affected families. The study recommended health education to the community, institute programs to screen patients, counseling, and community patients’ follow up. There was need to initiate home based income generation through micro financing.